1979
DOI: 10.1037/0278-7393.5.6.618
|View full text |Cite
|
Sign up to set email alerts
|

Abstraction of prototypical information by adults and 10-month-old infants.

Abstract: The primary purpose of this study was to investigate whether preverbal infants, when presented with exemplars of an artificially constructed category, would abstract a prototypical representation of the category, and if so, whether this representation was formed by either "counting" or "averaging" the features that were varying among category members. Two experiments are reported. In Experiment 1, a set of stimuli was developed and tested for which it was demonstrated that adult subjects would readily abstract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
116
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(122 citation statements)
references
References 20 publications
5
116
1
Order By: Relevance
“…It has been known for some time that infants are capable of abstracting prototypical information from schematic faces (Strauss, 1979). The ability that infants show in applying an averaging tool to more realistic face stimuli is per-haps not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for some time that infants are capable of abstracting prototypical information from schematic faces (Strauss, 1979). The ability that infants show in applying an averaging tool to more realistic face stimuli is per-haps not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, new items are categorized by direct comparison with the abstract prototype. Some evidence for this view comes from experiments in which adults and infants appear to find 'prototypical' items, which they have never seen, as familiar as -or occasionally even more familiar than -actual training items, especially after a delay of a week (e.g., Strauss 1979;Homa, Sterling and Trepel 1981). An alternative body of opinion views categorization as instance learning (see Chandler 2002, for a review).…”
Section: Psychologically Plausible Models Of Categorization In Grammamentioning
confidence: 99%
“…It is thought that humans form a mental prototype that is an average (or summation) of previous signals against which they compare a novel signal. Several studies have indicated that these prototypical representations are preferred over more extreme signals (Strauss 1979;Bomba & Siqueland 1983;Younger 1985;Quinn & Eimas 1986;Younger & Gotlieb 1988;Langlois & Roggman 1990). As prototypes for traits that show £uctuating asymmetry will be symmetrical, it could be predicted that symmetrical (average) signals should be preferred.…”
Section: Evolution Of Symmetry Preferencesmentioning
confidence: 99%